High-performance aluminum-nickel-lanthanum catalyst for carbon dioxide methanation and preparation method thereof

Through the micron nano-through-pore structure and high thermal conductivity of high-performance aluminum nickel lanthanum catalysts, the problem of accumulation of traditional catalysts at low temperature and high temperature hot spots is solved, and high-efficiency carbon dioxide methanation conversion and catalyst stability are achieved, which significantly improves catalytic activity and lifespan.

CN118649685BActive Publication Date: 2024-12-17SHANDONG HAIHUA GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411113992.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-14
Publication Date
2024-12-17
Estimated Expiration
2044-08-14

AI Technical Summary

Technical Problem

The existing carbon dioxide methanation catalyst has low catalytic activity at low temperatures, which can easily lead to hot spot accumulation and catalyst deactivation at high temperatures. In addition, traditional Ni-based catalysts have poor thermal conductivity, making it difficult to quickly remove reaction heat and product water, resulting in catalyst deactivation.

Method used

Using high-performance aluminum nickel lanthanum catalyst (AlNixLay) to prepare aluminum nickel lanthanum alloys with micron nano-through-hole structure and high thermal conductivity through induction smelting, leveraging the low solid solubility of Ni and La elements and the high activation ability of rare earth elements. A catalyst with a thermal conductivity higher than 180W/(m·K) is formed, and combined with aerosol powder making and alkali etching methods, the catalyst is ensured to efficient thermal conductivity and porous structure.

Benefits of technology

High-efficiency carbon dioxide conversion rate is achieved under normal pressure and 220°C, avoiding hot spots and carbon deposits, significantly improving the activity and life of the catalyst, and being better than traditional Ni/Al2O3 catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118649685B_ABST
    Figure CN118649685B_ABST
Patent Text Reader

Abstract

The present invention belongs to the field of energy and environmental catalysis, and specifically relates to a high-performance aluminum-nickel-lanthanum catalyst for the methanation of carbon dioxide and a preparation method thereof. The present invention firstly utilizes a high-speed and high-pressure gas atomization process to prepare an aluminum-nickel-lanthanum alloy powder, and then selectively removes some Al atoms therein to prepare a high-thermal-conductivity spherical catalyst particle powder having micron-nano through-hole structure characteristics, which has excellent carbon dioxide methanation catalytic performance and catalytic life under mild reaction conditions of normal pressure and 220°C. The raw materials used for preparing the catalyst provided by the present invention are low-cost and easy to obtain, the preparation method is simple and efficient, and is suitable for large-scale process production operations, and has broad industrial application prospects and significant application value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of energy and environmental catalysis, and specifically relates to a high-performance carbon dioxide methanation aluminum-nickel-lanthanum catalyst and a preparation method thereof. Background Art

[0002] According to statistics, from 1850 to 2018, the use of fossil fuels was the culprit for the sharp increase in greenhouse gas emissions, of which carbon dioxide accounted for about three-quarters of the total greenhouse gas emissions, leading to a series of ecological and environmental problems such as global warming and ocean acidification. The energy problem and the ecological and environmental problem are equally serious. 2 It is cheap, easily available, abundant, renewable, clean and non-toxic, and is an ideal and high-quality carbon-1 resource for various high-value-added chemicals. Therefore, its reduction and conversion can not only alleviate the environmental problems caused by the greenhouse effect, but also provide a solution to the problem of energy depletion.

[0003] Catalytic hydrogenation of carbon dioxide can produce a variety of compounds, among which catalytic hydrogenation of carbon dioxide methanation is an effective way to utilize carbon resources. Methane, as the main component of natural gas, is a high-quality gas fuel that can be used to synthesize acetylene, ammonia, synthesis gas and many other chemical products, which can alleviate the increasing shortage of fossil energy to a certain extent. In addition, the distribution of natural gas in my country is uneven, so carbon dioxide methanation technology has important practical significance.

[0004] The carbon dioxide methanation reaction is also called the Sabatier reaction, and the reaction equation is as follows:

[0005] CO 2 +4H 2 →CH 4 +2H 2 O, ΔH = -252.9 kJ·mol -1

[0006] The reaction is thermodynamically favorable and exothermic (ΔG 298K =-130.8 kJ·mol -1 ), so from a thermodynamic point of view, low temperature is conducive to the reaction; however, 2 The reduction to methane has significant kinetic limitations, so catalysts are usually required to accelerate the reduction of CO to methane at relatively low temperatures. 2 The kinetic conversion reaction rate can only achieve a considerable methane yield. The selected catalyst must have good catalytic H 2 Molecules and CO 2 High activity and stability of molecular dissociation. Traditional catalysts take Ni-based catalysts as an example, Ni / Al 2 O 3The Ni catalyst is the most popular carbon dioxide methanation catalyst. Compared with other catalysts, Ni is cheap and has a high catalytic activity for carbon dioxide methanation reactions. However, Ni-based catalysts also have disadvantages. Such catalysts have low catalytic activity at low temperatures. When the reaction temperature is below 200°C, the formation of product methane is almost undetectable. When the temperature is higher than 300°C or under pressurized conditions, it shows a good carbon dioxide conversion rate. However, at this time, excessive reaction heat and poor thermal conductivity of the carrier material lead to the formation of local hot spots in the catalyst bed, which inactivates the active components of the catalyst. Invention patent CN 112387283 A discloses a Ni-based carbon dioxide low-temperature methanation catalyst and its preparation method. When reacting at normal pressure and 300°C, CO 2 The conversion rate is 72%, and the activity remains high within 160 hours, but the methanation reaction temperature is relatively high. Invention patent CN 111514889 A discloses a ruthenium-based carbon dioxide hydrogenation methanation catalyst and its preparation method. The temperature is first raised to 400°C in a fixed bed reactor at normal pressure, and the catalyst is reduced for 3 hours under a hydrogen atmosphere. A molar ratio of H 2 :CO 2 :N 2 =4:1:5 raw gas, CO at 220℃ 2 The highest conversion rate is 49.8%, but the small reserves and high price of the precious metal ruthenium make it difficult to apply it on a large scale. 2 The conversion rate is low.

[0007] According to calculations, under normal operating conditions of the methanogenation system, for every 1 mol% of CO converted 2 , an adiabatic temperature rise of about 59.2°C is generated, and the maximum adiabatic temperature can reach 600°C, which corresponds to CO 2 The thermal equilibrium temperature between the exothermic methanation reaction and the endothermic reverse water gas shift reaction is that once the thermal disturbance caused by the accumulation of heat in the catalyst bed exceeds the binding energy between the Ni nanoparticles and the carrier, the well-dispersed Ni nanoparticles will migrate on the catalyst bed and further agglomerate into large particles driven by the surface energy. 2 The high concentration of steam in the hydrogenation product exacerbates the sintering of Ni. In addition, as the reaction proceeds, carbon deposition is prone to occur on the catalyst surface, especially on the exposed nickel active sites, which blocks the surface active sites and catalyst pores, and eventually leads to catalyst deactivation. Therefore, it is urgent to quickly remove the high-temperature hot spots and reaction product water of the methanation reaction, inhibit the thermal effects of the reaction process and the adverse effects of sintering and oxidation of the active sites caused by a large amount of product water, provide a carbon dioxide methanation catalyst with high catalytic activity and high catalytic stability, and develop an inexpensive catalyst preparation method that is easy to achieve large-scale production. Summary of the invention

[0008] In order to address the shortcomings and deficiencies of the prior art, the primary purpose of the present invention is to provide a high-performance carbon dioxide methanation aluminum-nickel-lanthanum catalyst with higher catalytic conversion activity and catalytic life.

[0009] The purpose of the present invention is achieved through the following technical solutions:

[0010] The chemical formula of the high-performance aluminum-nickel-lanthanum catalyst for carbon dioxide methanation is AlNi x La y , wherein, in terms of molar ratio, 0.05≤x≤0.2, 0.015≤y≤0.1. The phase composition of the aluminum-nickel-lanthanum catalyst is α-Al, Al 3 Ni and La 3 Al 11 Phase, α-Al, Al 3 Ni and La 3 Al 11 The weight proportions of the phases are 59.08-77.21 parts, 6.74-25.82 parts and 5.92-31.54 parts respectively.

[0011] The aluminum-nickel-lanthanum catalyst has a micron-nano through-hole structure, the α-Al phase constitutes a network-like skeleton matrix, and the Al 3 Ni and La 3 Al 11 phase embedded in the α-Al framework and the inner wall of the through-hole; the micron-nano through-hole structure of the catalyst and the Al 3 Ni, La 3 Al 11 The mosaic structure of the phase on the inner wall of the through hole is formed by selectively removing some Al atoms and Al 3 Ni, La 3 Al 11 It is obtained by the Al atoms in the

[0012] The thermal conductivity of the aluminum-nickel-lanthanum catalyst is 182-201 W / (m·K).

[0013] Another object of the present invention is to provide a method for preparing the above-mentioned high-performance aluminum-nickel-lanthanum carbon dioxide methanation catalyst. The method for preparing the high-performance aluminum-nickel-lanthanum carbon dioxide methanation catalyst comprises the following steps:

[0014] (1) Weigh the raw aluminum block, nickel block and lanthanum block according to the atomic ratio of Al: Ni: La =1: x: y (5≤x≤20%, 1.5≤y≤10%);

[0015] (2) The raw materials prepared in step (1) are sequentially placed in an induction melting furnace and smelted under argon protection to obtain AlNi x La y Alloy melt;

[0016] (3) pouring the alloy melt obtained in step (2) into a tundish with a φ5 mm leak hole at the bottom through a draft tube, and simultaneously starting atomization with high-pressure nitrogen;

[0017] (4) After atomization, the powder is completely cooled and sieved under a nitrogen atmosphere to obtain spherical AlNi x La y Alloy powder.

[0018] (5) The alloy powder with a particle size of 15 to 45 μm after screening in step (4) is selectively partially etched in an alkaline solution, and after etching, it is repeatedly washed and vacuum dried to obtain a spherical particle powder of an aluminum-nickel-lanthanum catalyst, and the average particle size D50 of the powder is 15 to 25 μm.

[0019] The purity of the raw material aluminum block, nickel block and lanthanum block in step (1) is ≥99%.

[0020] In step (2), the raw materials are placed in the order of aluminum block, nickel block and lanthanum block; the induction melting furnace is evacuated to 1.0~2.0×10 -3 Pa; the pressure range of protective gas argon is 1.0~1.2×10 5 Pa; melting temperature range 1300~1450℃.

[0021] The pressure range of nitrogen in step (3) is 1.5-10.0 MPa; the atomizer used is a supersonic tightly coupled annular gap spray disc.

[0022] The pressure range of the protective gas nitrogen in step (4) is 1.0~1.2×10 5 Pa.

[0023] In step (5), the time used for etching the alloy powder is 0.5-2.0 h, the etching temperature is 30-60° C., and the alkaline solution used is a 1.0-2.0 mol / L sodium hydroxide aqueous solution.

[0024] Compared with the prior art, the present invention has the following advantages:

[0025] The invention is innovative in that the high-performance carbon dioxide methanogenization and high-thermal conductivity aluminum-nickel-lanthanum alloy catalyst with a thermal conductivity of more than 180W / (m·K) utilizes the extremely low solid solubility of Ni and La elements in Al to ensure the high-efficiency thermal conductivity of the aluminum-nickel-lanthanum alloy catalyst, thus overcoming the inherent defects of the traditional Ni-based catalyst, such as low thermal conductivity and poor heat transfer performance (Ni's thermal conductivity at room temperature is 91.7W / (m·K) and Al's thermal conductivity is 91.7W / (m·K). 2 O 3The thermal conductivity of the carrier is only 25W / (m·K), which fundamentally ensures that the large amount of heat energy released by the carbon dioxide methanation reaction is quickly dissipated from the catalyst bed, avoiding the formation of hot spots and carbon deposits in the bed. The rare earth elements La and Ni have high efficiency in activating CO 2 Molecule and H 2 The second inventiveness of the present invention is to improve the efficient mass transfer characteristics of the catalyst through the micron-nano pore structure and Al 3 Ni, La 3 Al 11 The mosaic structure of the phase on the inner wall of the through hole is achieved by selectively removing some Al atoms and Al 3 Ni, La 3 Al 11 The Al atom in the alkali solution reacts to form 2Al+2H 2 O+2OH – →2AlO 2 – +3H 2 ↑, the Al atoms on the surface of the alloy are first dissolved to form a porous aluminum-less shell. At this time, the aluminum atoms inside the particles are tightly bound by the surrounding nickel atoms, and the reaction speed of the outer Al atoms is faster. They are completely removed within a certain period of time. At this time, the outer porous nickel shrinks and splits due to the action of surface tension, and grows into multiple nickel single crystals rich in lattice defects surrounding the particles, making the microstructure of the inner wall surface of the through hole rougher and rich in a large number of defective active sites. At the same time, there is a large amount of chemically adsorbed hydrogen on the surface of the catalyst with high activity specific surface area, and most of them are reversibly adsorbed Ni-H and La-H active components with weaker effects. This adsorbed hydrogen can participate in the hydrogenation reaction and accelerate the methanation reaction of carbon dioxide; the dispersion of high catalytically active metal Ni is improved, the surface metal Al completely disappears, and the skeleton structure of the catalyst is more stable; the large number of micrometer-nanometer through-hole structures of the catalyst ensure the smooth discharge of high-concentration steam during the methanation conversion reaction, which significantly improves the catalytic activity of the catalyst.

[0026] The high-performance carbon dioxide methanation and high-thermal-conductivity aluminum-nickel-lanthanum alloy catalyst provided by the present invention with a thermal conductivity of more than 180 W / (m·K) is applied to a carbon dioxide methanation conversion reaction under mild conditions, and can obtain relatively excellent catalytic conversion performance under mild conditions of normal pressure and 220° C., and the highest carbon dioxide conversion rate can reach 78.83%. No gas products other than methane are detected in the gas chromatography, and after 100 hours of methanation conversion reaction, the catalytic activity of the high-thermal-conductivity aluminum-nickel-lanthanum alloy catalyst remains stable and basically unchanged; the aluminum-nickel-lanthanum catalyst bed has efficient heat and mass transfer characteristics, avoiding the occurrence of heat accumulation and carbon deposition during the conversion reaction, and at the same time, a large number of micron-nano through-hole structures of the catalyst ensure the smooth discharge of high-concentration steam during the methanation conversion reaction, which significantly improves the catalytic activity of the catalyst, and is significantly superior to the conventional carbon dioxide methanation catalyst Ni / Al 2 O 3 , with higher catalytic conversion activity and catalytic life.

[0027] The preparation method of aerosol powder preparation + alkali solution etching adopted by the present invention is simple and efficient, the alkali solution used for etching can be recycled and pollution-free, the raw materials Al, Ni and La used are all conventional and easily available element components, suitable for process operation and large-scale industrial production, and has broad industrial application prospects and significant application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is the X-ray diffraction (XRD) pattern of the catalyst powder prepared in Example 1;

[0029] Figure 2 The scanning electron microscope (SEM) morphology of the catalyst powder prepared in Example 2;

[0030] Figure 3 The scanning electron microscope (SEM) morphology of a single particle of the catalyst powder prepared in Example 3;

[0031] Figure 4 The scanning electron microscope (SEM) morphology of the cross section of a single particle of the catalyst powder prepared in Example 3;

[0032] Figure 5 The catalyst prepared in Example 1 and the comparative example Ni / Al 2 O 3 Comparison chart of catalyst reaction bed temperature rise;

[0033] Figure 6 The catalyst prepared in Example 1 and the comparative example Ni / Al 2 O 3 Comparison chart of catalyst catalytic activity life;

[0034] Figure 7The catalyst prepared in Example 1 and the comparative example Ni / Al 2 O 3 Comparison of CO2 conversion rates at different temperatures (catalyst activity evaluation was carried out on a fixed-bed reactor at atmospheric pressure. A thermocouple was inserted in the middle of the reaction bed in the quartz glass tube reactor to monitor the actual temperature of the reaction bed. The reaction gas H 2 / CO 2 The molar ratio is 4. The reaction tail gas is condensed to remove the water vapor produced by the reaction, and then passed through a drying tube (filled with CaSO 4 After drying, the exhaust gas was fed into an Agilent online gas chromatograph (Agilent 7890A) for real-time online analysis to determine the CO 2 Gas products and CO from methanation reaction 2 conversion rate). DETAILED DESCRIPTION

[0035] For a better understanding of the present invention, the present invention is further described below in conjunction with the accompanying drawings and embodiments. However, the protection scope of the present invention is not limited to the description scope of the embodiments.

[0036] In the following embodiments of the present invention, the induction melting furnace used is composed of a melting power supply, an induction coil, a melting crucible, etc., which are located together with the tundish in a closed circular melting furnace body, and the furnace body is provided with vacuum and gas filling pipeline interfaces. Example 1

[0037] Weigh the raw aluminum block, nickel block and lanthanum block with purity ≥99% according to the molar ratio of Al: Ni: La =1: 0.2: 0.05, put them into the induction melting furnace in the order of aluminum block, nickel block and lanthanum block, close the door of the induction melting furnace, and evacuate the furnace to 1.0×10 -3 Pa, and fill the furnace with 1.0×10 5 Pa pressure argon, under the protection of argon, the temperature is raised to 1400℃ for smelting to obtain an alloy melt; the obtained alloy melt is poured into a tundish with a φ5mm leak hole at the bottom through a guide pipe, and then a N2 pressure of 6.0MPa is opened. 2 Start atomization, the atomizer used is a supersonic tightly coupled annular gap spray disk; after the atomization is completed, wait for the powder to cool completely, at 1.0×10 5 Pa pressure nitrogen atmosphere was used to screen and obtain AlNi 0.2 La 0.05 Spherical powder, the average particle size of the powder D50 is 25μm; the alloy powder with a particle size of 20-40μm after screening is selectively partially etched in a 1.5mol / L sodium hydroxide aqueous alkaline solution, the etching time is 2.0h, the etching temperature is 60℃, and after etching, it is repeatedly washed and vacuum dried to obtain the following Figure 1The phase composition shown is α-Al, Al 3 Ni and La 3 Al 11 AlNi 0.2 La 0.05 Catalyst spherical particle powder, α-Al, Al 3 Ni and La 3 Al 11 The weight percentages of the phases are 59.08%, 25.82% and 15% respectively. 0.2 La 0.05 The catalyst has micron-nano pores and Al 3 Ni, La 3 Al 11 The structural characteristics of the phase are embedded in the inner wall of the through hole, and the α-Al phase constitutes a network skeleton matrix. 0.2 La 0.05 Micron-nanopore structure of catalyst and Al 3 Ni, La 3 Al 11 The mosaic structure of the phase on the inner wall of the through hole is formed by selectively removing some Al atoms and Al 3 Ni, La 3 Al 11 It is obtained by the Al atoms in the sample, and the thermal conductivity is 182W / (m·K). Figure 5 In this embodiment, AlNi 0.2 La 0.05 Catalyst and Comparative Example Ni / Al 2 O 3 Comparison of the temperature rise of the catalyst bed at different methanation reaction temperatures. 2 O 3 The temperature rise of the catalyst reaction bed is above 20°C, and the AlNi 0.2 La 0.05 The temperature rise of the catalyst bed is limited to 1~3℃, indicating that AlNi 0.2 La 0.05 The construction of high thermal conductivity catalyst significantly reduces the existence of local hot spots, AlNi 0.2 La 0.05 The large number of micron and nano-pore structures of the catalyst ensure the smooth discharge of high-concentration steam during the methanation conversion reaction; AlNi 0.2 La 0.05 Under the mild conditions of atmospheric pressure and 220°C, the maximum carbon dioxide conversion rate of the catalyst can reach 78.83%. No gas products other than methane were detected in the gas chromatography. After 100 hours of methanogenic conversion reaction, AlNi 0.2 La 0.05The catalytic activity of the catalyst remains stable and basically unchanged, such as Figure 6 This embodiment AlNi 0.2 La 0.05 Catalyst and Comparative Example Ni / Al 2 O 3 Catalyst catalytic activity life comparison chart shows that the traditional Ni / Al 2 O 3 The maximum carbon dioxide conversion rate of the catalyst at atmospheric pressure and 220°C was only 18.92%, indicating that AlNi 0.2 La 0.05 The catalyst bed has more efficient heat and mass transfer characteristics, thus having higher catalytic conversion activity and catalytic life. Figure 7 In this embodiment, AlNi 0.2 La 0.05 Catalyst and Comparative Example Ni / Al 2 O 3 Comparison of carbon dioxide conversion rates at different temperatures shows that AlNi 0.2 La 0.05 The catalyst has a carbon dioxide conversion rate of 18.3% at atmospheric pressure and 150°C, while the conventional Ni / Al 2 O 3 The catalyst has not started to convert carbon dioxide at normal pressure and 150°C, but the carbon dioxide conversion rate increases significantly with increasing temperature. Example 2

[0038] Weigh the raw aluminum block, nickel block and lanthanum block with a purity of ≥99.5% according to the molar ratio of Al: Ni: La =1: 0.05: 0.1, put them into the induction melting furnace in the order of aluminum block, nickel block and lanthanum block, close the door of the induction melting furnace, and evacuate the furnace to 1.5×10 -3 Pa, and fill the furnace with 1.1×10 5 Pa pressure argon, under the protection of argon, the temperature is raised to 1300℃ for smelting to obtain an alloy melt; the obtained alloy melt is poured into a tundish with a φ5mm leak hole at the bottom through a guide pipe, and then a N2 pressure of 1.5MPa is opened. 2 Start atomization, the atomizer used is a supersonic tightly coupled annular gap spray disk; after the atomization is completed, wait for the powder to cool completely, at 1.1×10 5 Pa pressure nitrogen atmosphere was used to screen and obtain AlNi 0.05 La 0.1 Spherical powder, the average particle size of powder D50 is 30μm, such as Figure 2As shown in the figure, the alloy powder with a particle size of 15-35 μm after screening was selectively partially etched in a 2.0 mol / L sodium hydroxide aqueous alkaline solution. The etching time was 1.5 h and the etching temperature was 50 ° C. After etching, it was repeatedly washed and vacuum dried to obtain a phase composition of α-Al, Al 3 Ni and La 3 Al 11 AlNi 0.05 La 0.1 Catalyst spherical particle powder, α-Al, Al 3 Ni and La 3 Al 11 The weight percentages of the phases are 61.72%, 6.74% and 31.54% respectively. 0.05 La 0.1 The catalyst has micron-nano pores and Al 3 Ni, La 3 Al 11 The structural characteristics of the phase are embedded in the inner wall of the through hole, and the α-Al phase constitutes a network skeleton matrix. 0.05 La 0.1 Micron-nanopore structure of catalyst and Al 3 Ni, La 3 Al 11 The mosaic structure of the phase on the inner wall of the through hole is formed by selectively removing some Al atoms and Al 3 Ni, La 3 Al 11 The thermal conductivity is 191W / (m·K), AlNi 0.05 La 0.1 The catalyst has a large number of micron and nanometer through-hole structures to ensure the smooth discharge of high-concentration steam during the methanation conversion reaction. 0.05 La 0.1 Catalyst and Comparative Example Ni / Al 2 O 3 The comparative analysis of the temperature rise of the reaction bed of the catalyst at different methanation reaction temperatures shows that the comparative example Ni / Al 2 O 3 The temperature rise of the catalyst reaction bed is above 20°C, and the AlNi 0.05 La 0.1 The temperature rise of the catalyst bed is limited to 1~3℃, indicating that AlNi 0.05 La 0.1 The construction of high thermal conductivity catalyst significantly reduces the existence of local hot spots; AlNi 0.05 La 0.1Under the mild conditions of atmospheric pressure and 220°C, the maximum carbon dioxide conversion rate of the catalyst can reach 71.4%, and no gas products other than methane are detected in the gas chromatography. After 100 hours of methanogenic conversion reaction, AlNi 0.2 La 0.05 The catalytic activity of the catalyst remains stable and basically unchanged, such as Figure 6 This embodiment AlNi 0.2 La 0.05 Catalyst and Comparative Example Ni / Al 2 O 3 Catalyst catalytic activity life comparison chart shows that the traditional Ni / Al 2 O 3 The maximum carbon dioxide conversion rate of the catalyst at atmospheric pressure and 220°C was only 18.92%, indicating that AlNi 0.05 La 0.1 The catalyst bed has more efficient heat and mass transfer characteristics, thus having higher catalytic conversion activity and catalytic life. Example 3

[0039] Weigh the raw aluminum block, nickel block and lanthanum block with purity ≥99% according to the molar ratio of Al: Ni: La =1: 0.1: 0.015, put them into the induction melting furnace in the order of aluminum block, nickel block and lanthanum block, close the door of the induction melting furnace, and evacuate the furnace to 2.0×10 -3 Pa, and fill the furnace with 1.2×10 5 The alloy melt is smelted under the protection of argon gas with a pressure of 1450°C to obtain an alloy melt; the obtained alloy melt is poured into a tundish with a φ5mm leak hole at the bottom through a guide pipe, and then a N2 gas with a pressure of 10.0MPa is opened. 2 Start atomization, the atomizer used is a supersonic tightly coupled annular gap spray disk; after the atomization is completed, wait for the powder to cool completely, at 1.2×10 5 Pa pressure nitrogen atmosphere was used to screen and obtain AlNi 0.2 La 0.05 Spherical powder, the average particle size of the powder D50 is 15μm; the alloy powder with a particle size of 30-50μm after screening is selectively partially etched in a 0.5mol / L sodium hydroxide aqueous alkaline solution for 0.5h, the etching temperature is 30℃, and after etching, it is repeatedly washed and vacuum dried to obtain a phase composition of α-Al, Al 3 Ni and La 3 Al 11 AlNi 0.1 La 0.015 Catalyst spherical particle powder, such as Figure 3 AlNi 0.2 La 0.05The scanning electron microscope image of a single spherical catalyst powder shows the through-hole pores formed by selective local etching of alkali solution on the surface of the particle. Figure 4 In this embodiment, AlNi 0.2 La 0.05 The scanning electron microscope (SEM) morphology of the cross section of a single particle of the catalyst powder shows that the α-Al phase inside the spherical particle forms a network-like skeleton matrix. 3 Ni and La 3 Al 11 The microstructure morphology of the phase embedded in the α-Al skeleton and the inner wall of the through hole, α-Al, Al 3 Ni and La 3 Al 11 The weight percentages of the phases are 77.21%, 16.87% and 5.92% respectively. 0.1 La 0.015 The catalyst has micron-nano pores and Al 3 Ni, La 3 Al 11 The structural characteristics of the phase are embedded in the inner wall of the through hole, and the α-Al phase constitutes a network skeleton matrix. 0.1 La 0.015 Micron-nanopore structure of catalyst and Al 3 Ni, La 3 Al 11 The mosaic structure of the phase on the inner wall of the through hole is formed by selectively removing some Al atoms and Al 3 Ni, La 3 Al 11 The thermal conductivity is 201W / (m·K), AlNi 0.1 La 0.015 The catalyst has a large number of micron and nanometer through-hole structures to ensure the smooth discharge of high-concentration steam during the methanation conversion reaction. 0.1 La 0.015 Catalyst and Comparative Example Ni / Al 2 O 3 The comparative analysis of the temperature rise of the reaction bed of the catalyst at different methanation reaction temperatures shows that the comparative example Ni / Al 2 O 3 The temperature rise of the catalyst reaction bed is above 20°C, and the AlNi 0.1 La 0.015 The temperature rise of the catalyst bed is limited to 1~3℃, indicating that AlNi 0.1 La 0.015 The construction of high thermal conductivity catalyst significantly reduces the existence of local hot spots; AlNi 0.1 La 0.015Under the mild conditions of atmospheric pressure and 220°C, the maximum carbon dioxide conversion rate of the catalyst can reach 73.81%. No gas products other than methane were detected in the gas chromatography. After 100 hours of methanogenic conversion reaction, AlNi 0.1 La 0.015 The catalytic activity of the catalyst remains stable and basically unchanged. 2 O 3 The maximum carbon dioxide conversion rate of the catalyst at atmospheric pressure and 220°C was only 18.92%, indicating that AlNi 0.1 La 0.015 The catalyst bed has more efficient heat and mass transfer characteristics, thus having higher catalytic conversion activity and catalytic life.

[0040] Comparative Example

[0041] Take the commercially available Ni / Al with a nickel weight percentage of 40% 2 O 3 The catalyst has a maximum carbon dioxide conversion rate of 18.92% under mild conditions of atmospheric pressure and 220°C. No gaseous products other than methane are detected in the gas chromatography. After 100 hours of methanation reaction, the catalytic activity remains stable and basically unchanged. The Ni / Al catalyst under different methanation reaction temperatures 2 O 3 Catalyst reaction bed temperature rise test shows that Ni / Al 2 O 3 The temperature rise of the catalyst reaction bed is above 20°C. As the carbon dioxide methanation conversion reaction continues, the heat accumulation will inevitably lead to the generation and spread of hot spots, thereby causing the migration, aggregation and growth of active nickel catalytic sites, ultimately having an adverse effect on the catalytic activity and catalytic life.

Claims

1. A high performance aluminum-nickel-lanthanum carbon dioxide methanation catalyst, characterized in that: The chemical formula of the high-performance aluminum-nickel-lanthanum catalyst for carbon dioxide methanation is AlNi x La y , wherein, in terms of molar ratio, 0.05≤x≤0.2, 0.015≤y≤0.1; the phase composition of the aluminum-nickel-lanthanum catalyst is α-Al, Al3Ni and La3Al 11 Phase, α-Al, Al3Ni and La3Al 11 The weight parts of the phases are 59.08-77.21 parts, 6.74-25.82 parts, and 5.92-31.54 parts, respectively; The aluminum-nickel-lanthanum catalyst has a micron-nano through-hole structure, the α-Al phase constitutes a network-like skeleton matrix, and the Al3Ni and La3Al 11 phase embedded in the α-Al framework and the inner wall of the through hole; the micron-nano through-hole structure of the catalyst and the Al3Ni, La3Al 11 The mosaic structure of the phase on the inner wall of the through hole is formed by selectively removing some Al atoms in the α-Al matrix and Al3Ni, La3Al 11 AlNi x La y The thermal conductivity of the alloy catalyst is 182~201W / (m·K).

2. The method for preparing a high-performance carbon dioxide methanation aluminum-nickel-lanthanum catalyst according to claim 1, characterized in that: The steps include: (1) Weigh the raw aluminum block, nickel block and lanthanum block according to the atomic ratio of Al:Ni:La=1:x:y, where 0.05≤x≤0.2 and 0.015≤y≤0.1; (2) The raw materials prepared in step (1) are sequentially placed in an induction melting furnace and smelted under argon protection to obtain AlNi x La y Alloy melt; (3) pouring the alloy melt obtained in step (2) into a tundish with a φ5 mm leak hole at the bottom through a draft tube, and simultaneously starting atomization with high-pressure nitrogen; (4) After atomization, the powder is completely cooled and sieved under a nitrogen atmosphere to obtain spherical AlNi x La y Alloy powder; (5) The alloy powder with a particle size of 15 to 45 μm after screening in step (4) is selectively partially etched in an alkaline solution, and after etching, it is repeatedly washed and vacuum dried to obtain a spherical particle powder of an aluminum-nickel-lanthanum catalyst, and the average particle size D50 of the powder is 15 to 25 μm.

3. The method for preparing a high-performance aluminum-nickel-lanthanum carbon dioxide methanation catalyst according to claim 2, characterized in that: In step (2), the raw materials are placed in the order of aluminum block, nickel block and lanthanum block; the induction melting furnace is evacuated to 1.0~2.0×10 -3 Pa; the pressure range of protective gas argon is 1.0~1.2×10 5 Pa; melting temperature range 1300~1450℃.

4. The method for preparing a high-performance aluminum-nickel-lanthanum carbon dioxide methanation catalyst according to claim 2, characterized in that: The pressure range of nitrogen in step (3) is 1.5-10.0 MPa; the atomizer used is a supersonic tightly coupled annular gap spray disc.

5. The method for preparing a high-performance aluminum-nickel-lanthanum carbon dioxide methanation catalyst according to claim 2, characterized in that: The pressure range of the protective gas nitrogen in step (4) is 1.0~1.2×10 5 Pa.

6. The method for preparing a high-performance aluminum-nickel-lanthanum carbon dioxide methanation catalyst according to claim 2, characterized in that: In step (5), the time used for etching the alloy powder is 0.5-2.0 h, the etching temperature is 30-60° C., and the alkaline solution used is a 0.5-2.0 mol / L sodium hydroxide aqueous solution.